An Evolutionary Model for Sustainable Design - Caldas, Luisa (2011)
This paper presents a new generative design system to be used by architects in early to intermediate stages of design in order to help improve the environmental performance of buildings. The system was applied to a building designed by Alvaro Siza , to test its capability to handle complex architectural designs and to generate solutions within given criteria.